An energy resolved neutron imaging detector based on boron doped nMCP coupled with a time stamping optical camera - Tan, Jinhao; Song, Yushou; Zhou, Jianrong; Yang, Wenqin; Jiang, Xingfen; Zhou, Xiaojuan; Xia, Yuanguang; Liu, Shulin; Yan, Baojun; Liu, Hui; Wang, Songlin; Sun, Zhijia; et al. (Journal of instrumentation, 2024)
Energy resolved neutron imaging has developed rapidly due to its advantage on testing the inner structure of crystal samples. Neutron detector is one of the key components to determine the imaging results quality. The neutron sensitive microchannel plate (nMCP) has been widely used in energy resolved neutron imaging experiments because of the high spatial and timing resolution. However, the ability to adjust field-of-view (FOV) and spatial resolution has not been realized in the nMCP detector, which is an attractive capability in energy resolved neutron imaging experiments. In this paper, an energy resolved neutron imaging detector was developed by coupling nMCP with a time stamping camera. The neutrons were absorbed by nMCP and converted into light through a phosphor screen. Then the light was focused on the camera by optical lens. A data algorithm was designed to improve the data quality. By changing the magnification of the optical lens, large FOV (46mm diameter) and high spatial resolution (26 μm) were realized in the experiments at CSNS beamline 20. The energy resolved ability was demonstrated by a Bragg-edge transmission imaging experiment for aluminum and stainless-steel samples. The performance of this detector makes it a promising candidate used in energy resolved neutron imaging.